Highly malignant routine EEG predicts poor prognosis after cardiac arrest in the Target Temperature Management trial. (October 2018) - Backman, S.; Cronberg, T.; Friberg, H.; Ullén, S.; Horn, J.; Kjaergaard, J.; Hassager, C.; Wanscher, M.; Nielsen, N.; Westhall, E.
Abstract: Introduction: Routine EEG is widely used and accessible for post arrest neuroprognostication. Recent studies, using standardised EEG terminology, have proposed highly malignant EEG patterns with promising predictive ability. Objectives: To validate the performance of standardised routine EEG patterns to predict neurological outcome after cardiac arrest. Methods: In the prospective multicenter Target Temperature Management trial, comatose cardiac arrest patients were randomised to different temperature levels (950 patients, 36 sites). According to the prospective protocol a routine EEG was performed in patients who remained comatose after the 36 h temperature control intervention. EEGs were retrospectively reviewed blinded to outcome using the standardised American Clinical Neurophysiology Society terminology. Highly malignant, malignant and benign EEG patterns were correlated to poor and good outcome, defined by best achieved Cerebral Performance Category up to 180 days. Results: At 20 sites 207 patients had a routine EEG performed at median 76 h after cardiac arrest. Highly malignant patterns (suppression or burst-suppression with or without discharges) had a high specificity for poor outcome (98%, CI 92–100), but with limited sensitivity (31%, CI 24–39). Our false positive patient had a burst-suppression pattern during ongoing sedation. A benign EEG, i.e. continuous normal-voltage background without malignant features, identified patients with good outcome with 77% (CI 66–86) sensitivity and 80% (CI 73–86) specificity. Conclusion: Highly malignant routine EEG after targeted temperature management is a strong predictor of poor outcome. A benign EEG is an important indicator of a good outcome for patients remaining in coma.